The relationship between transversus abdominis and internal oblique thickness and disease-related characteristics in Parkinson's disease: An ultrasound-based study - Burcin Aktar; Seher Ozyurek; Evrim Goz; Berril Donmez Colakoglu; Birgul Balci (Neurological Sciences and Neurophysiology, 2023)
Background and Aim: The core muscles are essential for spinal stability during functional activities. Trunk muscle function is affected by specific neurodegenerative processes of Parkinson's disease (PD). This study aimed to investigate whether changes in transversus abdominis (TrA) and internal oblique (IO) thickness during the abdominal drawing-in maneuver (ADIM) were associated with clinical manifestations, core endurance, and functional mobility in patients with PD. Materials and Methods: We included patients with a modified Hoehn and Yahr staging of 3 or lower. TrA and IO muscle thickness were measured using ultrasound both at rest and during ADIM, and the percent change (%) was calculated to assess TrA and IO activation. Patients performed core endurance (prone bridge and sit-ups) and functional mobility tests (timed “up and go” [TUG] and five times sit-to-stand [FTSTS]). All assessments were conducted during the “on” phase. Results: Five female and 17 male patients were included in this study. We found a statistically significant correlation between ultrasound parameters of IO and the clinical manifestations of PD (P < 0.05). Correlations were observed between TrA percent change and prone bridge, sit-ups, TUG, and FTSTS (P < 0.05). Conclusion: To the best of our knowledge, this is the first ultrasound imaging-based study to demonstrate the relationship between TrA and IO muscle thickness and clinical outcomes, and functional performance in patients with PD. Percentage changes in IO were associated with the clinical manifestations of PD. Increased activation of TrA during ADIM was associated with improved core endurance and mobility. The results suggest that a trunk-specific exercise program may be the cornerstone in the treatment of PD-related changes.